The Training and Use of Service Dogs in Occupational Therapy Education - Mary Isaacson ATP, Ed.D., OTR/L (Scholarworks @ WMU, 2013)
The purpose of this study is to describe the role of occupational therapy fieldwork students in the training of service dogs. Ethnography is an approach that strives to explore and describe the point of view of people. Ethnographers view the researcher as an instrument to gain insight into the subject. This researcher utilizedher own experiences as an occupational therapist, an occupational therapy educator, and as a volunteer dog trainer of service dogs. She then validated the process through interviews with key informants. The results indicate that occupational therapists and occupational therapy students are capable of playing a significantrole in the training and placement of service dogs. During a level I experience, occupational therapy students experienced the importance that a dog can play in a person's life as a tool of adaptation. They also learned advocacy and professionalism and applied the Person-Environment-Occupation model of practice. In addition, students recognized that barriers exist in the use of service dogs.